A Shot at Economic Prosperity: Long-Term Effects of India's Childhood Immunization Program on Earnings and Consumption Expenditure - Amit Summan; Arindam Nandi; David E. Bloom (Institute of Labor Economics (IZA), 2022)
Routine childhood vaccinations are among the most cost-effective interventions. In recent years, the broader benefits of vaccines, which include improved cognitive and schooling outcomes, have also been established. This paper evaluates the long-term economic benefits of India's national program of childhood vaccinations, known as the Universal Immunization Programme (UIP). We combine individual-level data from the 68th round of the National Sample Survey of India (2011–2012) with district-wise data on the rollout of UIP in 1985–1990. We employ age-district fixed effects regression models to compare the earnings and per capita household consumer spending of 21- to 26-year-old adults who were born in UIP-covered districts vis-à-vis non-UIP districts in 1985–1990. We find that exposure to UIP in infancy increases weekly wages by 13.8% (95% CI: 7.6% to 20.3%, p<0.01) and monthly per capita household consumption expenditure by 2.9% (95% CI: 0.7% to 5.0% , p<0.01). Program exposure also reduces the probability that an individual's household relies on agriculture as the main source of income by 1.9% (95% CI: 0.0% to 3.5%, p<0.01). The findings are robust to several specifications, including varying study duration and accounting for potential migration. The effects vary by sex, location, and caste groups.
Keywords: I15; I18; J31; J38; 330; India; child immunization; health; wages